PENGARUH BLENDED LEARNING BERBASIS GOOGLE CLASSROOM DI KELAS DIGITAL TERHADAP HASIL BELAJAR PADA MATERI LITOSFER SISWA SMA NEGERI 8 KOTA PADANG - Yenastia Ananda Sobarni; Ernawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to examine the impact of implementing a Google Classroom-based Blended Learning model on students’ learning outcomes in lithosphere material. The study employed a quantitative approach using a quasi-experimental method wit a non- equivalent control Group Design. The participants were divided into an experimental group and a control group. Data were gathered through pre-test and post-test instruments\. The analysis procedures included tests of normality, homogeneity, and hypothesis testing using the Independent Sample T-Test. The findings revealed a statistically significant difference between the two groups, with a significance value of 0,000 (<0,05). The experimental group obtained higher post-test scores compared to the control group. Therefore, the implementation of Google Classroom-based Blended Learning has a significant effect on improving student’s learning outcomes.